Wood biomass in Serbia – Resources and possibilities of use. Issue 8 (2nd August 2016) - Janevski, Jelena N.; Stojanović, Branislav V.; Laković, Mirjana S.; Stojiljković, Mirko M.; Mitrović, Dejan M.
ABSTRACT: Biomass is a renewable energy source that can be used as a substitute for fossil fuels in the production of heat. The current condition of renewable energy source in Serbia is bad although Serbia has good potential for development. The potential of forest biomass as another important resource of biomass in Serbia lies in the processing of 1.5 million cubic meters of forest growth per year in the form of segments, chips, and sawdust. Wood biomass is currently the most exploited energy. The primary purpose of this work is to show the potential and possibilities of wood biomass in Serbia (with particular reference to the southeastern region of Serbia), which is important for further development of the renewable energy sector. The results obtained in this work could be used as a reference for issues related to the production, sale, and research on wood biomass.